Evaluation of New born Stabilization Units in the Health Facilities in Uttarakhand, India - Anusha Sharma; Meenakshi Khapre; Surekha Kishore (Medsci Publications, 2020)
Background: Our country is adding to one-fifth of live births globally and an enormous number of neonatal deaths (<25%). In India, although the number of new-born stabilization units (NBSU) reported operational is increasing but there is lack of clarity of the role of NBSUs as well as suboptimal utilization and quality of services in these units. Material and method: A cross-sectional study was conducted from December 2017 to Jan 2018 in health facilities with functioning NBSUs in three blocks of Haridwar and two blocks in Tehri. Results: Out of total 2602 deliveries, 221 neonatal admissions were reported with an average length of stay at the hospital in most of the centres was one and a half-day. There were a limited number of trained doctors and nurses in the health facilities. The maximum deficit was found with the availability of resuscitator and oxygen cylinder (80%) followed by a digital thermometer (75%). Conclusion: To ensure essential care to the new-borns by keeping quality at the centre it is important to focus upon adequate number of medical staff, properly functioning equipment, continuous supply of medicines, regular training sessions and appropriate referral mechanism to higher centres.